(3LeGd GdCSHhYs - (3GdMSjfj, GHf WGhhS, GHf WGhhS, Ydj Hf ehSi Hf LYaQ GdMSjfj, J (B664(3g` (B1266(3es
(3ChdgG (B:s
(3ChdgG(B: (3MeOG ddg Ld LdGdg GdPj CjbX Phj GdSfI (B... (3hHYO aMjK aJM Gddg Ld LdGdg Ydi jO eedhcg (B.. (3aj Sdc YbhO ebUhO cfhR eG Ufag aj GJHGY eQGOgs
(3BNQgG (B:s
(3BNQgG(B: (3ef cGf YOh dc aj OfjGc hJQi ef gh Ohfc GdBf ebOeG Ydjc aj BNQGc(B. (3GdMeO ddg hEjGfG YfGjGJ GdeWGdH hTQafG HGdXaQ HeG gh LdG LdGdg Cgdg ef GdehGgHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 26s
(3GdPQjYI, L (B5: 92s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs